Rekabentuk dan implementasi sistem automasi pembotolan MAPS menggunakan programmable logic controller, PLC - Riza Sulaiman; Prabuwono; A.S; Denni Kurniawan; Syaimak Abdul Shukor (Universiti Kebangsaan Malaysia, 2009)
This paper discusses the design and implementation of Programmable Logic Controller (PLC) on Modular Automation Bottling Production System-MAPS. PLC is used for running a system so that it can work automatically and used on repeatable system application. The objectives of using PLC in industry are to minimize production cost, increase productivity, increase quality and system reliable. Design and implementation of this automation system uses MAPS. MAPS is a modular system that was developed by using a few stations into an integrated system. In this research, actual MAPS were used and integrates with other system such as detector, pneumatic, mechanic, electronic and control system.